A Positive Version of the Good Behavior Game in a Self-Contained Classroom for EBD: Effects on Individual Student Behavior. (February 2022) - Moore, Tara C.; Gordon, Jason R.; Williams, Angela; Eshbaugh, Jessica F.
A within-participant withdrawal design was used to examine the effects of a positive version of the Good Behavior Game (GBG) for three students in an elementary special education classroom for students with emotional or behavioral disorders (EBD). Results indicated immediate improvements in disruptive behavior and academic engagement for all three students when the GBG was implemented which was generally replicated in the second intervention phase for academic engagement. Tau- U effect sizes ranged from .76 to .95 indicating large and very large effects for both behaviors for two students and academic engagement for the third student, but Tau- U for the third student's disruptive behavior was .32 (considered not effective ). Two students exhibited slight decreasing trends in academic engagement behavior and increasing trends in disruptive behavior near the end of intervention phases. A preliminary within-session analysis also suggested students' behavior was generally better in intervention phases both during and not during the GBG when compared with their baseline levels of behavior. Social validity information suggested generally positive teacher and student perceptions about the GBG initially, with less positive student perceptions 10 weeks following the conclusion of the study. The teacher reported implementing the GBG 5 times over the 10 weeks following the conclusion of the study.